Smoking Cessation Advice“The Best Time to Quit Smoking was the Day you Started, the SecondBest Time to Quit is Today” - Abbas, Sana; Abbas, Beenish; Khan, Faisal Nawaz; Ehsan, Hafiz Rabi Ul; Malik, Ahsan; Malik, Sadia Munir (Pakistan Armed Forces Medical Journal, 2022)
Objective: To decide the mindfulness and competency of dental and clinical experts in offering smoking discontinuance guidance.Study Design: Cross-sectional study.Place and Duration of Study: Tertiary Care Teaching Institute, Rawalpindi Pakistan, from Oct 2019 to Feb 2020.Methodology: A pilot study carried out at 15-20 participants for questionnaire validation and reviewed by independent experts for face validity. A final questionnaire comprised of ten multiple-choice questions in addition to demographic profile. The minimum sample size required for the study was 261, where the national prevalence of smoking was 21.6%.Results: A total of 550 participants participated in the study and data were extracted from their responses. There were 335 (61.0%) males and 215 (39.0%) females in the study group, with a mean age of 32.4 ± 4.3 and the age range 25 – 44 years. Among total respondents, 380 (69%) were qualified dental and medical practitioners whereas 170(31%) were medical and dental students. Only (40%) respondents were confident in rendering cessation advice whereas (60%) were not. Only (15.5%) participants declared that they received formal training to counsel for quitting smoking. Among the total 234 (100%) males were confident in giving in advice whereas none of the females were sure enough p value